Dog-bite-related attacks: A new forensic approach. (May 2020) - Iarussi, Fabrizio; Cipolloni, Luigi; Bertozzi, Giuseppe; Sasso, Luigi; Ferrara, Michela; Salerno, Monica; Rubino, Giuseppe Tommaso Roberto; Maglietta, Francesca; Dinisi, Armida; Albano, Davide; Iarussi, Valerio; Pomara, Cristoforo; et al.
Highlights: Dog attacks today represent a health hazard. Aggressor dog identification is critical to ascertain the owner. This experimental study proposes a new forensic approach. Abstract: Dog attacks today represent a health hazard considering that prevention strategies have not always been successful. The identification of the dog that attacked the victim is necessary, considering the civil or criminal consequences for the animal's owner. An accurate scene analysis must be performed collecting a series of important information. Forensic investigations in dog attacks involve different methods, such as the evaluating of the canine Short Tandem Repeat (STR) typing in saliva traces on wounds or bite mark analysis, however, these techniques cannot always be applied. The effort to find new methods to identify the dog that attacked the victim represents a very interesting field for the forensic community. This study aims to propose an innovative approach, based on the identification of the victim's profile in the dog's mouth, using a buccal swab on the suspected aggressor dog, to find the victim's genetic profile. In addition, a further goal of this study is to determine the persistence time of hexogen DNA in the dog's mouth to define a timeframe for performing this particular technique. For this purpose, ten different dogs were used to aggressively bite a bovine sample (reference sample) to simulate the victim. For each dog two buccal swabs were taken at different time intervals: 30′, 45′, 60′, 90′, 120′, 150′, 180′ and 240′. The typing of the swabs provided an interpretable profile after 45′ while traces of bovine profile were found until 150′ after the dog attack simulation. These results could be improved using the human identification kit, which is more sensitive. In the light of this experimental study, the forensic community should consider using this approach in real casework studies with the aim of collecting new data, validating this technique for forensic use.